Mutation of C20orf7 Disrupts Complex I Assembly and Causes Lethal Neonatal Mitochondrial Disease - Sugiana, Canny (Elsevier, 2008)
Complex I (NADH:ubiquinone oxidoreductase) is the first and largest multimeric complex of the mitochondrial respiratory chain. Human complex I comprises seven subunits encoded by mitochondrial DNA and 38 nuclear-encoded subunits that are assembled together in a process that is only partially understood. To date, mutations causing complex I deficiency have been described in all 14 core subunits, five supernumerary subunits, and four assembly factors. We describe complex I deficiency caused by mutation of the putative complex I assembly factor C20orf7. A candidate region for a lethal neonatal form of complex I deficiency was identified by homozygosity mapping of an Egyptian family with one affected child and two affected pregnancies predicted by enzyme-based prenatal diagnosis. The region was confirmed by microcell-mediated chromosome transfer, and 11 candidate genes encoding potential mitochondrial proteins were sequenced. A homozygous missense mutation in C20orf7 segregated with disease in the family. We show that C20orf7 is peripherally associated with the matrix face of the mitochondrial inner membrane and that silencing its expression with RNAi decreases complex I activity. C20orf7 patient fibroblasts showed an almost complete absence of complex I holoenzyme and were defective at an early stage of complex I assembly, but in a manner distinct from the assembly defects caused by mutations in the assembly factor NDUFAF1. Our results indicate that C20orf7 is crucial in the assembly of complex I and that mutations in C20orf7 cause mitochondrial disease.